Factor VIII: C (FVIII: C) Recovery and Half-Life After Infusion of Steam-Treated High Purity Factor VIII Concentrate in Severe Hemophilia A - Comparison of One-Stage Assay, Two-Stage Assay and a Chromogenic Substrate Assay - Hellstern, Peter; Kiehl, Ralf; Miyashita, Chieko; Schwerdt, Holger; von Blohn, Gerhard; Köhler, Michael; Büttner, Maria; Wenzel, Ernst (Thrombosis and Haemostasis, 1986)
Factor VIII :C recovery and half-life was measured in 16 hemophilia A patients under comprehensively standardized conditions. Each patient received the same lot of a steam-treated high purity FVIII concentrate at a dose of 19-33 U/kg body weight. A comparison was made between the one-stage assay, the two-stage assay and a chromogenic substrate test for FVIII :C determination using a FXa-sensitive chromogenic substrate. Factor VIII :C potency of the administered FVIII concentrate was measured using calibration curves derived from a concentrate standard and FVIII: C plasma levels were read from calibration curves derived from a plasma standard. The chromogenic assay showed a good reproducibility at FVIII: C levels between 0.015 and 0.50 U/ml. The FVIII :C recoveries calculated from the results of the one-stage assay, the two-stage assay and the chromogenic substrate test were 109 ± 20, 92 ± 14 and 81 ± 11% (x ± SD), respectively. The elimination half-lives of FVIII :C were calculated by non-linear least square analysis using a modified computerized Gauss-Newton algorithm. The half-lives calculated from the FVIII: C plasma levels measured by the one-stage assay, the two-stage assay and the chromogenic test were 23.8 ± 6.4, 22.2 ± 5.7 and 17.1 ± 4.8 h (x ± SD), respectively. No previous study has reported such long half-life values. Our findings indicate that measurements of recoveries and half-lives by the chromogenic FVIII :C assay and by computerized nonlinear least square analysis allow the possibility of individualized FVIII replacement therapy.
Keywords: Factor VIII: C recovery; Factor VIII: C half-life; One-stage assay; Two-stage assay; Chromogenic substrate assay